Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Green wood bio-adhesives from cellulose-derived bamboo powder hydrochars - Yong-Xing Chen; Han-Song Zhu; Fan Gao; Huan-Ran Xiong; Huan Yang; Zhi-Xiang Xu; Pei-Gao Duan; Li-Jun Zheng; Sameh M. Osman; Rafael Luque (Chemical Engineering Journal, 2024)

Identification of New Transcription Factors that Can Promote Pluripotent Reprogramming - Ping Huang; Jieying Zhu; Yu Liu; Guihuan Liu; Ran Zhang; Dongwei Li; Duanqing Pei; Ping Zhu (Stem Cell Reviews and Reports, 2021)
Background Four transcription factors, Oct4, Sox2, Klf4, and c-Myc (the Yamanka factors), can reprogram somatic cells to induced pluripotent stem cells (iPSCs). Many studies have provided a number of alternative combinations to the non-Yamanaka factors. However, it is clear that many additional transcription factors that can generate iPSCs remain to be discovered. Methods The chromatin accessibility and transcriptional level of human embryonic stem cells and human urine cells were compared by Assay for Transposase-Accessible Chromatin with high-throughput sequencing (ATAC-seq) and RNA sequencing (RNA-seq) to identify potential reprogramming factors. Selected transcription factors were employed to reprogram urine cells, and the reprogramming efficiency was measured. Urine-derived iPSCs were detected for pluripotency by Immunofluorescence, quantitative polymerase chain reaction, RNA sequencing and teratoma formation test. Finally, we assessed the differentiation potential of the new iPSCs to cardiomyocytes in vitro. Results ATAC-seq and RNA-seq datasets predicted TEAD2, TEAD4 and ZIC3 as potential factors involved in urine cell reprogramming. Transfection of TEAD2, TEAD4 and ZIC3 (in the presence of Yamanaka factors) significantly improved the reprogramming efficiency of urine cells. We confirmed that the newly generated iPSCs possessed pluripotency characteristics similar to normal H1 embryonic stem cells. We also confirmed that the new iPSCs could differentiate to functional cardiomyocytes. Conclusions In conclusion, TEAD2, TEAD4 and ZIC3 can increase the efficiency of reprogramming human urine cells into iPSCs, and provides a new stem cell sources for the clinical application and modeling of cardiovascular disease. Graphical abstract

A novel missense mutation of $$ADAR1$$ ADAR 1 gene in a Chinese family leading to dyschromatosis symmetrica hereditaria and literature review - Shuai-Mei Liu; Meng-Xia Ni; Ming-Chao Zhang; Pei-Ran Zhu; Qiu-Yu Wu; Wei-Jun Jiang; Jing Zhang; Wei-Wei Li; Xin-Yi Xia (Journal of Genetics, 2017)

A new method for estimating effect size distribution and heritability from genome-wide association summary results - Lei Zhang; Yue-Ping Shen; Wen-Zhu Hu; Shu Ran; Yong Lin; Shu-Feng Lei; Yong-Hong Zhang; Christopher J. Papasian; Nengjun Yi; Yu-Fang Pei (Human Genetics, 2016)

Comparison of SPE, IFE, and FLC in Monitoring Patients with Multiple Myeloma After Autologous Stem Cell Transplantation - Wei Li; Jia-Zi Zhou; Hui-Rong Chang; Li-Jun Dai; Zi-Ling Zhu; Yu-Feng Feng; Fei-Ran Gong; De-Pei Wu (Cell Biochemistry and Biophysics, 2015)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Bivariate genome-wide association study suggests that the DARC gene influences lean body mass and age at menarche - Rong Hai; Lei Zhang; YuFang Pei; LanJuan Zhao; Shu Ran; YingYing Han; XueZhen Zhu; Hui Shen; Qing Tian; HongWen Deng (Science China Life Sciences, 2012)